Evolutionary characteristics of swine-origin H1N1 influenza virus that infected humans from sporadic to pandemic - Lei Han, Wenying Lu; Yifang Han; Shuhua Li; Jianhua Yin; Jiaxin Xie, Tong Su; Guangwen Cao (African Journal of Pig Farming, 2014)
Evolutionary process of swine-origin H1N1 influenza A viruses that infected humans from sporadic to pandemic is of high epidemiological significance but still remains obscure. To understand this process, we performed phylogenetic, bootscan, and adaptive evolution analyses using the sequences of the 8 gene segments from swine-origin H1N1 influenza A viruses that infected humans and the reference viruses. Classic swine H1N1 viruses occasionally infected humans before 1998. Sporadic human infection with the triple-reassortant swine-origin H1N1 viruses was firstly identified in 1998 and has become increasingly frequent since 2005. Except genes encoding the neuraminidase and matrix protein of swine influenza viruses of Eurasian lineage, other 6 genes of A/H1N1/2009 pandemic strain were most closely linked to those of A/Iowa/CEID23/2005(H1N1), a representative swine-origin triple-reassortant virus that infected humans sporadically. Potential positive selections acting on the haemagglutinin gene evolved from classic swine H1N1 viruses to the triple-reassortant H1N1 viruses and on the neuraminidase gene evolved from Eurasian swine viruses to A/H1N1/2009 pandemic viruses might play a role in cross-species transmission and human infection. Surveillance of genetic evolution of influenza A viruses in swine workers might provide useful clues of influenza pandemic.